Mighty, Mighty Construction Site - Rinker, Sherri Duskey; Lichtenheld, Tom (San Francisco : Chronicle Books, 2017)
Told in rhyming text, this story follows Excavator, Bulldozer, Crane Truck, Dump Truck, and Cement Mixer, who will need to work together as they tackle their biggest job yet--a massive building.
Keywords: Construction equipment -- Juvenile fiction; Trucks -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Construction equipment -- Fiction; Trucks -- Fiction; Cooperativeness -- Fiction; Stories in rhyme; Stories in rhyme